Leadership Styles Transform Productivity through Organizational Culture in Indonesia: Gaya Kepemimpinan Mengubah Produktivitas melalui Budaya Organisasi di Indonesia - Zulfa, Indana; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the impact of transformational and transactional leadership styles on employee productivity through organizational culture at IKM Culinary Kebab. Using a sample of 68 employees and statistical analysis via SPSS 20, the research found that transformational leadership directly enhances productivity, while its influence on organizational culture is insignificant. Conversely, transactional leadership significantly shapes organizational culture but does not directly affect productivity. Both leadership styles indirectly boost productivity through a strong organizational culture. These insights highlight the importance of fostering an effective organizational culture to maximize the benefits of different leadership styles in small-scale culinary businesses. Highlights: 1. Transformational leadership directly enhances employee productivity.2. Transactional leadership significantly influences organizational culture.3. Organizational culture mediates leadership styles' impact on productivity. Keywords: Transformational leadership, Transactional leadership, Employee productivity, Organizational culture, IKM Culinary Kebab